Construction of a 2D Graphene‐Like MoS2/C3N4 Heterojunction with Enhanced Visible‐Light Photocatalytic Activity and Photoelectrochemical Activity. Issue 14 (2nd February 2016) - Yan, Jia; Chen, Zhigang; Ji, Haiyan; Liu, Zheng; Wang, Xin; Xu, Yuanguo; She, Xiaojie; Huang, Liying; Xu, Li; Xu, Hui; Li, Huaming
Abstract: A novel graphene‐like MoS2 /C3 N4 (GL‐MoS2 /C3 N4 ) composite photocatalyst has been synthesized by a facile ethylene glycol (EG)‐assisted solvothermal method. The structure and morphology of this GL‐MoS2 /C3 N4 photocatalyst have been investigated by a wide range of characterization methods. The results showed that GL‐MoS2 was uniformly distributed on the surface of GL‐C3 N4 forming a heterostructure. The obtained composite exhibited strong absorbing ability in the ultraviolet (UV) and visible regions. When irradiated with visible light, the composite photocatalyst showed high activity superior to those of the respective individual components GL‐MoS2 and GL‐C3 N4 in the degradation of methyl orange. The enhanced photocatalytic activity of the composite may be attributed to the efficient separation of electron–hole pairs as a result of the matching band potentials between GL‐MoS2 and GL‐C3 N4 . Furthermore, a photocatalytic mechanism for the composite material has been proposed, and the photocatalytic reaction kinetics has been measured. Moreover, GL‐MoS2 /C3 N4 could serve as a novel sensor for trace amounts of Cu 2+ since it exhibited good selectivity for Cu 2+ detection in water. Abstract : MoS2 /C3 N4 heterojunction : A new type of graphene‐like MoS2 /C3 N4 composite has been prepared by a facile ethylene glycol‐assisted solvothermal treatment. The synergistic effect of face‐to‐face combination increases the contact area and makes charge transfer more efficient, thereby promoting the separation of electron–hole pairs and leading to an enhancement of the overall photoconversion efficiency (see picture).